Пучковая неустойчивость в левых средах - Аверков, Ю.О.; Яковенко, В.М. (Видавничий дім "Академперіодика" НАН України, 2007)
The instability of the infinitely thin electron beam that moves above the interface of vacuum left-handed material has been investigated theoretically. The absolute instability is shown to occur due to the interaction between the beam and the backward surface waves that propagate
along the interface. It has been established that, under certain parameters of the left-handed material, the electron beam can excite bulk electromagnetic waves.